Traffic Congestion at Road Intersections in Ilorin, Nigeria - Aderamo, Adekunle J.; Atomode, Tolu I. (Richtmann Publishing, 2012)
The paper examined traffic congestion problems and their causes at selected road intersections in Ilorin, Nigeria. Thecharacteristics of the intersections that predispose them to congestion problems and the spatial pattern of traffic congestion atthe road intersections were also identified. In addition, traffic volume and delays were estimated and causes of delays identified.Data were collected through direct field survey on intersection characteristics, traffic volume and composition, traffic delay andcauses and land use activities. Data were also collected from past research reports, journals, textbooks, maps and the Internet.The analysis of data collected revealed that spatio-temporal variations exist in traffic flows and delays at the studiedintersections. Also, traffic wardens and parking problems were found to be the greatest causes of delays at the roadintersections in the city. The study therefore recommends that the road intersections be signalized and vehicle parking be strictlyprohibited at road intersections to reduce traffic congestion and delays at road intersections in the city.